2011
DOI: 10.1002/jms.1877
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a liquid chromatography–tandem mass spectrometry method for the quantitation of synthetic cannabinoids of the aminoalkylindole type and methanandamide in serum and its application to forensic samples

Abstract: After the discovery of synthetic cannabimimetic substances in 'Spice'-like herbal mixtures marketed as 'incense' or 'plant fertilizer' the active compounds have been declared as controlled substances in several European countries. As expected, a monitoring of new herbal mixtures which continue to appear on the market revealed that shortly after control measures have been taken by legal authorities, other compounds were added to existing mixtures and to new products. Several compounds of the aminoalkylindole ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 22 publications
1
116
1
5
Order By: Relevance
“…Animal studies and a few human studies on the SC JWH-018 have shown that aminoalkylindoles are rapidly metabolized (19). Later studies and case reports with reported levels of other aminoalkylindoles, including JWH-073, JWH-081, JWH-250, AM-2201, and XLR-11, support this observation (20)(21)(22). Hydroxylation of the alkyl chain attached to the indole moiety and its subsequent oxidation to a carboxylic acid derivative are two of the major metabolic reactions undergone by aminoalkylindoles (19,23).…”
Section: Concentrations Of Adb-pinaca and Metabolite In Biologic Samplesmentioning
confidence: 90%
“…Animal studies and a few human studies on the SC JWH-018 have shown that aminoalkylindoles are rapidly metabolized (19). Later studies and case reports with reported levels of other aminoalkylindoles, including JWH-073, JWH-081, JWH-250, AM-2201, and XLR-11, support this observation (20)(21)(22). Hydroxylation of the alkyl chain attached to the indole moiety and its subsequent oxidation to a carboxylic acid derivative are two of the major metabolic reactions undergone by aminoalkylindoles (19,23).…”
Section: Concentrations Of Adb-pinaca and Metabolite In Biologic Samplesmentioning
confidence: 90%
“…[19,20] High performance liquid chromatography (HPLC) was used with various detectors to separate compounds between NPS classes [16] as well as within classes of cathinones [23] and cannabinoids. [24] In general, the techniques mentioned above require transport to a forensic laboratory and solvent dissolution/filtering before analysis. In contrast, vibrational techniques such as Fourier transform infrared (FT-IR), near infrared (NIR), and Raman spectroscopy can perform rapid analysis in the solid-state and are available in handheld and portable versions, which are advantageous for in-field testing for law enforcement and healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Most prevalent synthetic cannabinoids compounds are CP 47,497-C8, JWH-081, JWH-250, JWH-018 and JWH-073 (Gunderson et al 2012;Zawilska and Wojcieszak 2014). New-generation SCs include the hexyl homolog JWH-019 (Dresen et al 2011), the aminoalkylindoles JWH-073 (Lindigkeit et al 2009), JWH-250 (Westphal et al 2010) and JWH-398 (Hudson et al 2010) and JWH-015, JWH-122, HU-210 and AM-694 (EMCDDA 2009;Ernst et al 2011). More recently, 5f-AKB48 and 5F-PB-22 have been detected in both seizures and fatalities (Roussel et al 2015;Van Hout and Hearne 2017).…”
Section: Synthetic Cannabinoids (Sc)mentioning
confidence: 99%
“…More recently, 5f-AKB48 and 5F-PB-22 have been detected in both seizures and fatalities (Roussel et al 2015;Van Hout and Hearne 2017). These synthetic psychoactive compounds are sprayed or added to the herbal mixtures (Uchiyama et al 2010) generally sold in metal foil sachets containing 1-3 g of dried leaves, resin or flowers (Dresen et al 2011;Zuba et al 2011;Kikura-Hanajiri et al 2011;Zawilska and Wojcieszak 2014). Labelling on these herbal products often denotes 'not for human consumption' or 'for aromatherapy only' (Zawilska and Wojcieszak 2014).…”
Section: Synthetic Cannabinoids (Sc)mentioning
confidence: 99%